Results-Based Financing for Municipal Solid Waste - World Bank (Washington, DC, 2014)
Municipal Solid Waste (MSW) management is a crucial service provided by cities around the world, but is often inefficient and underperforming in developing countries. This report provides eight examples of RBF designs, each tailored to the specific context and needs of the solid waste sector in the specific city or country. These projects are currently in various stages of preparation or implementation; hence, lessons can be inferred only in terms of how solid waste projects can be developed using RBF principles. The eight examples could be classified into three main categories: (a) RBF to improve solid waste service delivery and fee collection: in Nepal and the West Bank, the projects use RBF subsidies to improve the financial sustainability of MSW services by increasing user fee collection while simultaneously improving waste collection services; (b) RBF to promote recycling and source separation: in the cases of China, Indonesia, and Malaysia, an incentive payment model is used to improve source separation and collection of waste through changes in behavior at the household level; and (c) RBF to strengthen waste collection and transport in under-served communities: in Mali and Tanzania, projects were designed to strengthen secondary waste collection and transport for under-served communities. In the case of Jamaica, the project was designed to improve waste collection in inner-city communities and to encourage waste separation as well as general neighborhood cleanliness. This report presents the challenges faced in the design and implementation phases as well as general recommendations on how to address such challenges in future projects. Some of the lessons learned and recommendations are generally applicable to the preparation of any MSW project, whereas others are particular to the design of RBF projects for MSW.